A Pragma-Dialectical Approach to Political Discourse Analysis: A Case Study of the Former United State Trade Representative Ron Kirk’s Remarks on the Poultry Case (Sinología hispánica. China Studies Review, 2016)
Under the research framework of Pragma-Dialectics, this paper analyses and evaluates theformer United State trade representative RonKirk’s remarks on the trade conflict of poultry.Through this case study, I intend to develop apragma-dialectical approach to the politicaldiscourse. Based on the argumentativereconstruction, strategic maneuvering analysisand critical evaluation of the remarks, thispaper finds that even if Ron Kirk’s remarks lookreasonable apparently, there are still somefallacies hidden in them. In order to make theUS government benefit most from the tradeconflict, after considering comprehensively ofthe potential topics, audience demands, andpresentational devices, Ron Kirk maneuversstrategically by choosing beneficial startingpoints and arranging argumentative schemestechnically. By doing so, he can transmit Anti-China ideology to the international societyimperceptibly. In addition, by taking intoconsideration the background information ofthe poultry case and the Ten Commandments ofa critical discussion, this paper reveals that, theaccepted starting points and the argumentschemes are abused in Ron Kirk’s remarks.Through the case study, this paper tries to studypolitical discourse from Pragma-Dialecticalapproach and provide feasible analyticalmethods and reasonable evaluative standardsfor the political discourse analysis, so that anew perspective will be offered for researcheson political discourse.